Speeding Up FPGA Placement via Partitioning and Multithreading. (23rd December 2009) - Ababei, Cristinel
Abstract : One of the current main challenges of the FPGA design flow is the long processing time of the placement and routing algorithms. In this paper, we propose a hybrid parallelization technique of the simulated annealing-based placement algorithm of VPR developed in the work of Betz and Rose (1997). The proposed technique uses balanced region-based partitioning and multithreading. In the first step of this approach placement subproblems are created by partitioning and then processed concurrently by multiple worker threads that are run on multiple cores of the same processor. Our main goal is to investigate the speedup that can be achieved with this simple approach compared to previous approaches that were based on distributed computing. The new hybrid parallel placement algorithm achieves an average speedup of2.5 × using four worker threads, while the total wire length and circuit delay after routing are minimally degraded.